Comparative studies on cardiac innate immunity - Linde, Annika (Kansas State University, 2008)
Background - Cardiovascular disease (CVD) impacts the lives of millions, and ranks as the number one killer world-wide. Despite significant research efforts, CVD remains a major burden on the national health care system, and novel therapeutic modalities to effectively and curatively fight many debilitating diseases of the heart and vasculature are urgently needed. The role of inflammation in the development of CVD has been increasingly in focus through the past decade. Elucidating upon the plethora of innate immune mechanisms likely involved in CVD therefore becomes of immediate interest. Host defense peptides (HDPs) are central elements of innate immunity, encompassing molecules (including the defensin peptides) with wide-reaching biological effects, including immunomodulation and antimicrobial activity. Hypothesis & Specific Aims - The study's main hypothesis relies upon the basic concept that the heart possesses a local innate defense system, which actively aids in fighting off a variety of "danger signals", and that a disarray in this defense contributes to development of CVD. The heart expresses beta-defensin peptides (BDs), and we theorized that these HDPs act as a local defense system within the myocardium - or in other words as "guardians of heart health". The specific aims of the experimental studies were to 1) Evaluate expression of cardiac BDs in response to inflammatory mediators, and 2) Assess the functional properties (including antimicrobial activity and immunomodulation) of synthetic BD peptides in vitro. Design & Methods - To test our hypothesis, we studied myocardial beta-defensin expression (rBDs) in a rat model, comparing levels among two experimental and one control group. Animals were exposed to lipopolysaccharide (LPS) or high-fat diet (HFD) intake - representative of exposure to either an infectious (LPS) or non-infectious (HFD) inflammatory mediator. Serum samples were collected for measurement of cytokines, inflammatory and cardiac biomarkers and lipid-profiling. Beta-defensin levels were assessed using customized Superarray assays and qRT-PCR, and all amplicon sizes on the PCR products were subsequently confirmed using agarose gel electrophoresis. Serum levels were assessed on commercial ELISA kits. Functional assessment of select rBDs included computational modeling as well as in vitro antimicrobial and cell migration assays. Results & Conclusion - Exposure to high-fat diet feeding for a period of three weeks resulted in a multifold-increase in cardiac mRNA expression of select rBDs, while short-term LPS exposure resulted in a smaller, but statistically non-significant, elevation in the myocardial expression of rBDs. Synthetic analogues of two naturally occurring cardiac rBDs were evaluated for in vitro activity. The synthetic rBD11 peptide exhibited antimicrobial activity against Staph aureus, and both rBDs exhibited chemoattraction of rat leukocytes. Our data suggests that rBDs might play a central role in the intrinsic immune mechanisms of the cardiovasuclar system, and possibly act as protectors of heart health.
Keywords: Biology, Veterinary Science (0778); Biology, Molecular (0307); Biology, Veterinary Science (0778)